EULAR recommendations for the management of psoriatic arthritis with pharmacological therapies: 2019 update. Issue 6 (20th May 2020) - Gossec, Laure; Baraliakos, Xenofon; Kerschbaumer, Andreas; de Wit, Maarten; McInnes, Iain; Dougados, Maxime; Primdahl, Jette; McGonagle, Dennis G; Aletaha, Daniel; Balanescu, Andra; Balint, Peter V; Bertheussen, Heidi; et al.
Abstract : Objective: To update the European League Against Rheumatism (EULAR) recommendations for the pharmacological treatment of psoriatic arthritis (PsA). Methods: According to the EULAR standardised operating procedures, a systematic literature review was followed by a consensus meeting to develop this update involving 28 international taskforce members in May 2019. Levels of evidence and strengths of recommendations were determined. Results: The updated recommendations comprise 6 overarching principles and 12 recommendations. The overarching principles address the nature of PsA and diversity of both musculoskeletal and non-musculoskeletal manifestations; the need for collaborative management and shared decision-making is highlighted. The recommendations provide a treatment strategy for pharmacological therapies. Non-steroidal anti-inflammatory drugs and local glucocorticoid injections are proposed as initial therapy; for patients with arthritis and poor prognostic factors, such as polyarthritis or monoarthritis/oligoarthritis accompanied by factors such as dactylitis or joint damage, rapid initiation of conventional synthetic disease-modifying antirheumatic drugs is recommended. If the treatment target is not achieved with this strategy, a biological disease-modifying antirheumatic drugs (bDMARDs) targeting tumour necrosis factor (TNF), interleukin (IL)-17A or IL-12/23 should be initiated, taking into account skin involvement if relevant. If axial disease predominates, a TNF inhibitor or IL-17A inhibitor should be started as first-line disease-modifying antirheumatic drug. Use of Janus kinase inhibitors is addressed primarily after bDMARD failure. Phosphodiesterase-4 inhibition is proposed for patients in whom these other drugs are inappropriate, generally in the context of mild disease. Drug switches and tapering in sustained remission are addressed. Conclusion: These recommendations provide stakeholders with an updated consensus on the pharmacological management of PsA, based on a combination of evidence and expert opinion.